Acute Lung Lesion Caused by Microvascular Thrombosis - A. M. Golubev; V. V. Moroz; D. V. Lysenko; G. N. Meshcheryakov; A. N. Kuzovlev (Общая реаниматология)
Objective. To assess a role of pulmonary microvascular thrombosis in the development of acute lung lesion.Material and methods. Experiments were carried out on 60 albino non-inbred male rats. Thromboplastin solution was injected into their jugular vein under anesthesia. Experiments lasted 1 hour to 3 days. Lung specimens were fixed in 10% neutral formaldehyde solution and poured into paraffin. Histological slices were stained with hema-toxylin-eosin; periodic acid Schiff reaction was made. Morphometrical and statistical studies were employed. Results. 1—3 hours after thromboplastin injection, there were thromboses in the lumens of minor arteries, capillaries, and veins, developed interstitial and intraalveolar edema, and diapedetic hemorrhages, epithelial desquamation into the bronchial lumen, as well as stab leukocytic infiltration of interalveolar septa. The magnitude of morphological changes in the lung is dissimilar in different animals.Conclusion. Pulmonary microvascular thrombosis leads to the development of acute lung lesion documented by morphological studies.